Whiteness Studies II - Peter Kolchin (Journal de la Société des Américanistes)
Whiteness Studies. Over the past two decades, scholars in the social sciences and humanities have increasingly focused on « whiteness » as a new way of exploring race and racism in America. These two articles evaluate the way historians have approached the subject. The first article, originally published in the Journal of American History in 2002, examines the development of whiteness studies in the 1990s, and the second, which appears here for the first time, provides an update on more recent trends. The articles find considerable potential in whiteness studies, but also point to serious conceptual and methodological problems that deserve attention.